The assessment of individual risk of radicalization and violent extremism - Vuković, Slaviša Lj. (NBP. Nauka, bezbednosti, policija, 2022)
Modern counter-terrorism strategies include, among other preventive mechanisms, assessing the risk of radicalization and violent extremism. Undoubtedly, this is a very important preventive mechanism that should enable the timely identification of potentially dangerous individuals against whom further measures and actions should be taken to prevent them from joining terrorist groups or organizations and carrying out a terrorist attack. Although it is already well known that there is no universal profile of a terrorist, which doesn’t support the efforts to establish reliable instruments for assessing the risk of radicalization and violent extremism, it is the fact that an increasing number of such instruments have been used in risk assessment and positive results are expected from them. The aim of this paper is to indicate the possibilities of practical application of such instruments based on the analysis of their characteristics as well as possible limitations. Such observations could be useful to national practitioners to improve risk assessment of potential threats, as well as to researchers to encourage and develop further research that is certainly a necessity in this domain.
Keywords: radicalization, extremism, individual risk, assessment